2011
DOI: 10.1080/02705060.2011.555204
|View full text |Cite
|
Sign up to set email alerts
|

Precision of aging structures for Indian major carp,Cirrhinus mrigala, from the River Ganga

Abstract: Scales, opercular bones, otoliths, vertebrae, and dorsal fin rays were compared to ascertain the best aging structure of Cirrhinus mrigala. All structures showed alternating opaque and translucent bands that were interpreted as annuli; however, structures differed greatly in the clarity of their presumed annual marks. Age estimates were compared by calculating the percentage of agreement (PA), average percentage of error (APE), and coefficient of variation (CV) and by constructing age bias plots. Age estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…2012; Silver Carp Hypophthalmichthys molitrix : CV = 15%, Khan et al. 2015; Largemouth Bass: CV ≤ 22%, Tyszko and Pritt 2017; Lake Sturgeon: CV = 12–18%, Izzo et al. 2021; Blue Sucker: CV = 12%, Radford et al.…”
Section: Discussionmentioning
confidence: 99%
“…2012; Silver Carp Hypophthalmichthys molitrix : CV = 15%, Khan et al. 2015; Largemouth Bass: CV ≤ 22%, Tyszko and Pritt 2017; Lake Sturgeon: CV = 12–18%, Izzo et al. 2021; Blue Sucker: CV = 12%, Radford et al.…”
Section: Discussionmentioning
confidence: 99%
“…The time required to process and read vertebrae made them less practical to use but that precision and accuracy involved with vertebrae made them the best among the three structures (vertebrae, otoliths, and scales) for the age estimation of Oncorhynchus keta (Clark 1987). Researchers have reported that rings present on vertebral centra were not very clear and showed numerous minute marks unrelated to cyclic events in fishes such as Makaira nigricans (Hill et al 1989), Boops boops (Khemiri et al 2005) and Cirrhinus mrigala (Khan et al 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…The use of scales moved rapidly from discovery to application during the first quarter of the last century (Lee, 1920;Carlander, 1987). Several studies on scales for age and growth determination of Indian fishes have been undertaken (Kagwade, 1971;Hanumantha Rao, 1974;Singh and Sharma, 1995;Deepak et al, 2008;Khan, 2009 andKhan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%